Olives and olive oil production in the Alto Ricaurte climate region in Boyaca, Colombia - Ruiz S., Leonardo Mauricio; Carvajal R., Diana Carolina; Garcia M., José Francisco; Almanza-Merchán, Pedro José (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The olive tree has expanded to several countries because of its easy adaptation to difficult edapho-climatic zones and  high culinary and medicinal interest given the physicochemical composition of its fruit, including Argentina, Chile, Peru and Mexico, which have similar soil and climate conditions to the Mediterranean, where the phenological stages correspond to  clearly distinct climatic seasons. However, in the Alto Ricaurte region in Boyaca, Colombia, olives do not set because of the tropical climate conditions. Because of these characteristics, the behavior of some trees, sown 4 to 30 years ago in this region, were evaluated. The temperature and precipitation were measured, and 20 branches were selected per tree, which were monitored from appearance until development; the polar and equatorial diameter of the fruits were measured until reaching maturation. A fruit and oil analysis was carried out with olives harvested in two maturation states in 2017. The temperature had a positive correlation with the phenological stages in a range of 11 to 29°C, which directly influenced the development of inflorescences and their performance. In the same year, there were two or more blooms with different intervals, where the same branch had inflorescences, flowers, freshly filled fruits and other mature fruits. As for the characteristics of the fruit and the oil, it was evident that the content of fatty acids was within the parameters required by the International Olive Council.